Priorities in the location of multiple public facilities - Olivier Bochet; Sidartha Gordon (University of Bern, Department of Economics, 2008)
A collective decision problem is described by a set of agents, a profile of single-peaked preferences over the real line and a number k of public facilities to be located. We consider public facilities that do not suffer from congestion and are non-excludable. We provide a characterization of the class of rules satisfying Pareto-efficiency, object-population monotonicity and sovereignty. Each rule in the class is a priority rule that selects locations according to a predetermined priority ordering among interest groups. We characterize each of the subclasses of priority rules that respectively satisfy anonymity, hiding-proofness and strategy-proofness. In particular, we prove that a priority rule is strategy-proof if and only if it partitions the set of agents into a fixed hierarchy. Alternatively, any such rule can be viewed as a collection of fixed-populations generalized peak-selection median rules (Moulin, 1980), that are linked across populations, in a way that we describe.
Keywords: D60; D63; D70; D71; H41; 330; Multiple public facilities; Priority rules; Hierarchical rules; Object-population-monotonicity; Sovereignty; Anonymity; Strategy-proofness; Generalized median rules; Hiding-proofness; Entscheidungstheorie; Wahlverhalten; Öffentliche Güter; Pareto-Optimum; Theorie